Water Pump Speed Control System Using ESP32 and Blynk: Sistem Pengatur Kecepatan Pompa Air Menggunakan ESP32 dan Blynk - Hamzah Maulana; Arief Wicaksono (Universitas Muhammadiyah Sidoarjo, 2026)
General Background The advancement of Internet of Things technology enables automation and remote control of electrical devices in daily applications. Specific Background Water pumps using AC motors generally operate at fixed speeds, limiting user flexibility in adjusting water usage. Knowledge Gap However, practical implementation of remote-based speed control systems for single-phase AC water pumps using integrated IoT platforms remains limited. Aims This study aims to design and implement a water pump speed control system using an ESP32 microcontroller, AC light dimmer, and Blynk application for remote operation. Results The system successfully regulates pump speed through a smartphone interface, where higher slider percentages correspond to increased voltage and motor rotation, with test results showing 25% producing 1.4V (slow), 35% producing 1.6V (slow), 50% producing 2.1V (medium), and 80% producing 2.7V (fast). Novelty The proposed system integrates ESP32-based control with a mobile IoT platform and dimmer-based voltage regulation in a simple minimum system configuration. Implications This system provides a practical solution for flexible water usage control and supports the development of smart home-based automation systems Keywords: Water Pump, ESP32, Blynk, AC Dimmer, Speed Control Key Findings Highlights Slider adjustment directly changes electrical input and rotation level Wireless interface enables remote operation through mobile device Prototype operates consistently under repeated testing conditions